Ազգային անվտանգության հարացույցի հստակեցման հիմնախնդիրը նոր աշխարհակարգի ձևավորման գործընթացում - Աղայան, Նարինե (Լիմուշ հրատ.)
The article examines the challenges and problems faced by the Republic of Armenia in the tense situation that has developed in the South Caucasus region. It is noted that the republic is faced with the task of clarifying and understanding its own place and role in the region and in general in the emerging new world order, as well as restoring its subjectivity. It is noted that in the conditions of international geopolitical chaos, there has been a need to reassess allied relations, take measures to find new foreign policy partners and clarify foreign policy priorities in accordance with the new situation. The author of the article notes that the biggest challenge facing the Republic of Armenia today is the Turkish-Azerbaijani threat, to counter which our country needs reliable allies with whom we have common interests.
Keywords: Քաղաքագիտություն